Native Speaker Video toward Students’ Speaking Skill at Elementary Class: an Experimental Study - Faizatul Muyassaroh; Musdalifah Musdalifah; Nuril Firdaus; Raudhatul Islam (Jurnal Ilmiah Multidisipin, 2026)
Speaking is one of the important skill for the students in learning English. It has five components such as grammar, vocabulary, comprehension, fluency and pronunciation. Since speaking is imperative, numerous students have to master speaking as well as they can. In truth, speaking is not simple to be mastered. Therefore the student's speaking skill are low. It is trusted that the teacher as an educator will be able to apply an assortment of media, so the students can overcome their difficulties. Native speaker video in language learning is an elective to be able to enhance students’ speaking skill. The aim of this research used native speaker video was to measure the effect of native speaker video toward students’ speaking skill at elementary level. This research used quantitative method especially pre-experimental research one group pre-test and post-test design. The data collection used test. The data analysis were Normality test and t-test. The Normality test was normal 0.424 > 0.05, while t-test was significant 0.000 < 0.05. Furthermore, the use of native speaker video gave a better speaking score toward students’ speaking skill.